The role of renewables and nuclear energy in Turkey's Vision 2023 energy targets: Economic and technical scrutiny - Melikoğlu, Mehmet (Pergamon-Elsevier Science Ltd, 2016)
The Turkish government aims to produce 30% of the country's electricity demand from renewable energy sources and put two nuclear power plants with nearly 10,000 MW total installed capacity into operation by 2023. In this study, the cost of renewable energy investments based on the Vision 2023 energy targets are calculated in detail, and it is found that Turkey should spend on average 61.0 billion US$ to renewable energy sources to fulfil the Vision 2023 energy targets. Current analysis also clearly showed that Turkey must draw an urgent roadmap to illustrate how it is going to finance these mammoth renewable energy investments. It is also pinpointed that Turkey would spend nearly 50.0 billion US$ to its two new nuclear power plants in the next decade. Thus totalling the renewable and nuclear energy investments to nearly 110 billion US$ or approximately 90% of Turkey's estimated energy spending by 2023. Also, detailed analysis of the literature showed that only 2400 MW of the anticipated nuclear capacity can be put into operation by 2023. Consequently, a slight delay in the Vision 2023 energy targets can be expected if no urgent action is taken by the Turkish government. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cost analysis; Energy policy; Nuclear energy; Vision 2023; Renewable energy; Turkey